Principal components analysis of agitation outcomes in Alzheimer's disease. (August 2016) - Yesavage, Jerome A.; Taylor, Joy L.; Friedman, Leah; Rosenberg, Paul B.; Lazzeroni, Laura C.; Leoutsakos, Jeannie-Marie S.; Kinoshita, Lisa M.; Perlow, Mark J.; Munro, Cynthia A.; Devanand, D.P.; Drye, Lea T.; Mintzer, Jacobo E.; et al.
Abstract: Background: We developed a composite measure of agitation as a secondary outcome of change over time in the Citalopram for Agitation in Alzheimer's disease study (CitAD). CitAD demonstrated a positive effect of citalopram on agitation on the Neurobehavioral Rating Scale agitation subscale (NBRS-A). CitAD included additional agitation measures such as the Cohen-Mansfield Agitation Inventory and the Neuropsychiatric Inventory. Methods: We performed principal components analyses on change in individual item of these scales for the same, original CitAD subjects. Results: The first principal component accounted for 12.6% of the observed variance and was composed of items that appear to reflect agitation. The effect size for citalopram calculated using this component was 0.53 (95% CI 0.22–0.83) versus 0.32 for the NBRS-A (95% CI 0.01–0.62). Conclusions: Results suggest that a composite measure of change in agitation might be more sensitive than change in a single primary agitation measure. Highlights: We developed a composite measure of agitation as an outcome of change over time. We performed principal components analysis. The composite agitation measure might be more sensitive than a single such measure.